DIGITAL TRANSFORMATION AND PAPUAN MICRO BUSINESS COMPETITIVENESS IN BIAK NUMFOR - Karina Arfany Arfah; Patma Tuasikal (Gema Kampus IISIP YAPIS Biak, 2026)
Digital transformation has become an important determinant in strengthening the competitiveness of micro-enterprises amid changing consumer behavior and the rapid expansion of technology-based economies. This study aims to analyze how social media-based marketing strategies are implemented by Indigenous Papuan micro-entrepreneurs and how these strategies contribute to business competitiveness in Biak Numfor Regency. The study employs a descriptive qualitative approach focusing on Indigenous Papuan micro-enterprises operating in local culinary businesses, cultural handicrafts, and small-scale trade. Data were collected through in-depth interviews, observation, and documentation, while data analysis followed the stages of data reduction, data display, and conclusion drawing. The findings reveal that digital transformation among Indigenous Papuan micro-enterprises remains in an early adaptation phase, yet it has positively contributed to market expansion, stronger customer interaction, local product identity reinforcement, and promotional efficiency. The most dominant platforms are WhatsApp Business, Facebook, and Instagram, which are used for visual promotion, direct communication, and product information dissemination. However, limited digital literacy, inadequate marketing content quality, internet access constraints, and weak business management remain major obstacles. The study implies that digital business mentoring, contextual social media marketing training, and affirmative policies are necessary to support Indigenous Papuan micro-enterprises in building sustainable competitiveness in both local and regional markets